ASSESSMENT OF KNOWLEDGE, ATTITUDES AND PRACTICE REGARDING NEEDLES STICKS INJURIES AMONG NURSES IN DISTRICT PESHAWAR (The Research of Medical Science Review, 2025)
Introduction: Needle stick an injury is a wound or cut that is generated by needles that accidentally rip or puncture the skin. This can result in contact with tainted blood and the fluids of the body. Needle stick injuries are very harmful for the health care workers and it may cause severe infections diseases. Objective: The study aims is to categorize and identify the knowledge, practice and attitudes about needle stick injuries among nurses. Methodology: a cross-sectional study was carried out in district Peshawar. Participants were recruited from LRH, KTH and HMC. Data was collected from overall, 230 nurses. Permission was granted from the university and participants before collecting of the data. Data was collected using an adopted questionnaire. Results: Overall, 230 participants were recruited in the study. The majority of the participants were from the age group 20 to 30 years.136 of the participants were female while the majority (59%) of the nurses was holding BSN degree. Overall, 71% participants were reported Poor knowledge, 70% participants were reported unsatisfactory practices and 74% participants were reported unsatisfactory attitude regarding needle stick injuries. Conclusion: The findings of the study concluded that the nurses had poor knowledge towards needle stick injuries; also they have unsatisfactory practices and attitude towards needle stick injuries.